Optimalisasi Kinerja Inovasi: Mengungkap Pengaruh Intellectual Capital Terhadap Nilai Perusahaan - Anis Chariri; Imelda Dea Savila (Politeknik Ganesha Medan, 2025)
The purpose of this study is to create a model that can determine how innovation performance is useful as a moderating variable in the relationship between intellectual capital and the value of a company. In this study, purposive sampling technique was used to select a sample of companies listed on the Indonesia Stock Exchange from 2019 to 2023. This study uses a quantitative descriptive approach, this method examines intellectual capital using the Value Added Intellectual Coefficient (VAIC), the value of a company is calculated using Tobin's Q ratio, and innovation performance is measured by looking at R&D expenditure. In addition to applying a quantitative descriptive approach, this study also used the multivariate regression analysis method to test the relationship between the research variables. The findings of this study are that although intellectual capital acts as a crucial strategic resource, its effect on firm value is not always direct. This indicates that companies need to optimize innovation performance to harness the potential of their intellectual capital. Effective innovation is able to convert intellectual capital into products or processes that have real value, and further contribute to increasing the competitiveness and value of the company in the market.